Early impact of robot-assisted partial nephrectomy on renal function as assessed by renal scintigraphy. Issue 2 (June 2016) - Luciani, Lorenzo; Chiodini, Stefano; Donner, Davide; Cai, Tommaso; Vattovani, Valentino; Tiscione, Daniele; Giusti, Guido; Proietti, Silvia; Chierichetti, Franca; Malossini, Gianni
Abstract To measure the early impact of robot-assisted partial nephrectomy (RAPN) on renal function as assessed by renal scan (Tc 99m-DTPA), addressing the issue of risk factors for ischemic damage to the kidney. All patients undergoing RAPN for cT1 renal masses between June 2013 and May 2014 were included in this prospective study. Renal function as expressed by glomerular filtration rate (GFR) was assessed by Technetium 99m-diethylenetriaminepentaacetic acid (Tc 99m-DTPA) renal scan preoperatively and postoperatively at 1 month in every patient. A multivariable analysis was used for the determination of independent factors predictive of GFR decrease of the operated kidney. Overall, 32 patients underwent RAPN in the time interval. Median tumor size, blood loss, and ischemia time were 4 cm, 200 mL, and 24 min, respectively. Two grade III complications occurred (postoperative bleeding in the renal fossa, urinoma). The GFR of the operated kidney decreased significantly from 51.7 ± 15.1 mL/min per 1.73 m2 preoperatively to 40, 12 ± 12.4 mL/min per 1.73 m2 1 month postoperatively (p = 0.001) with a decrease of 22.4 %. On multivariable analysis, only tumor size (p = 0.05) was a predictor of GFR decrease of the operated kidney. Robotic-assisted partial nephrectomy had a detectable impact on early renal function in a series of relatively large tumors and prevailing intermediate nephrometric risk. A mean decrease of 22 % of GFR as assessed by renal scan in the operated kidney was found at 1 month postoperatively. In multivariable analysis, tumor size only was a significant predictor of renal function loss.